CoDNaS-Q: a database of conformational diversity of the native state of proteins with quaternary structure - Escobedo, N.; Tunque Cahui, R.R.T.; Caruso, G.; Ríos, E.G.; Hirsh, L.; Monzon, A.M.; Parisi, G.; Palopoli, N. (Oxford University Press, 2022)
Abstract Summary A collection of conformers that exist in a dynamical equilibrium defines the native state of a protein. The structural differences between them describe their conformational diversity, a defining characteristic of the protein with an essential role in multiple cellular processes. Since most proteins carry out their functions by assembling into complexes, we have developed CoDNaS-Q, the first online resource to explore conformational diversity in homooligomeric proteins. It features a curated collection of redundant protein structures with known quaternary structure. CoDNaS-Q integrates relevant annotations that allow researchers to identify and explore the extent and possible reasons of conformational diversity in homooligomeric protein complexes. Availability and implementation CoDNaS-Q is freely accessible at http://ufq.unq.edu.ar/codnasq/ or https://codnas-q.bioinformatica.org/home. The data can be retrieved from the website. The source code of the database can be downloaded from https://github.com/SfrRonaldo/codnas-q.
Keywords: Protein quaternary structure; Diversity (politics); Conformational isomerism; Protein structure; Computer science; Functional diversity; Source code; Computational biology; Resource (disambiguation); Database; Biology; Chemistry; Programming language; Biochemistry; Molecule; https://purl.org/pe-repo/ocde/ford#1.06.00